The association between parental attitudes and alcohol consumption and adolescent alcohol consumption in Southern Ireland: a cross-sectional study - Eimear Murphy; Ian O'Sullivan; Derry O'Donovan; Ann Hope; Martin P. Davoren (BMC, 2016)
Abstract Background Alcohol plays a complex role in society. A recent study showed that over half of Irish adults drink hazardously. Adolescents report increased levels of alcohol consumption. Previous research has inferred the influence of the parent on their adolescent. Thus, the aim of the current study was to investigate the association between adolescent alcohol consumption and their parent's consumption pattern and attitude toward alcohol use in Southern Ireland. Methods A cross-sectional survey was undertaken in November 2014. This involved distributing a survey to adolescents (n = 982) in their final two years of second level education and at least one of their parents from a local electorate area in Southern Ireland. This survey included: alcohol use, self- reported height and weight, smoking status, mental health and well-being along with attitudinal questions. Chi-square tests and multivariate logistic regression were utilised. Results A 37 % response rate was achieved. Over one-third (34.2 %) of adolescents and 47 % of parents surveyed reported hazardous drinking. Over 90 % of parents disagreed with allowing their adolescent to get drunk and rejected the idea that getting drunk is part of having fun as an adolescent. The majority (79.5 %) of parents surveyed believed that their alcohol consumption pattern set a good example for their adolescent. Multivariate logistic regression highlights the association between adolescent hazardous alcohol consumption and hazardous drinking by the father. Furthermore either parent permitting their adolescent to drink alcohol on special occasions was associated with hazardous alcohol consumption in the adolescent. Conclusion The findings of this research notes a liberal attitude to alcohol and increased levels of consumption by the parent are linked to hazardous adolescent drinking behaviour. Future action plans aimed at combatting adolescent hazardous alcohol consumption should also be aimed at tackling parents' attitudes towards and consumption of alcohol.